Impact of Project-Based Learning on Grade Ten Students’ Mathematics Achievement - Dahal, Prem Prasad; G. C., Laxmi (Journal of Research in Education, 2025)
The present study analyze the effect of Project Based Learning (PBL) on the achievement of Mathematics of the Grade Ten students in Kathmandu and Lalitpur districts. A sample of 214 students from four secondary schools was chosen. Data were gathered using a structured questionnaire which was based on the Perception towards Mathematics Inventory (PTMI) and were analyzed using descriptive statistics, correlation and regression. Results indicated that students had positive perceptions of PBL, especially the value that they placed on collaboration and mathematics as it is applied in the real world. Correlation analysis showed that there were significant and strong positive relationships between the variables of project commitment, mathematics self-efficacy and mathematics achievement. The results of regression analysis further supported the notion that Projects and Confidence were important predictors of students’ mathematics achievement, but with Projects being a stronger predictor. The findings indicate that PBL is a valuable alternative to the traditional teaching method and that it is effective in increasing the achievement in mathematics as well as in improving the confidence level of the students. Recommendations include the systematic implementation of PBL in the secondary school mathematics curriculum with teacher training and resources provided by the schools.